Enzyme Shielding in an Enzyme‐thin and Soft Organosilica Layer. Issue 21 (9th April 2016) - Correro, M. Rita; Moridi, Negar; Schützinger, Hansjörg; Sykora, Sabine; Ammann, Erik M.; Peters, E. Henrik; Dudal, Yves; Corvini, Philippe F.‐X.; Shahgaldian, Patrick
Abstract: The fragile nature of most enzymes is a major hindrance to their use in industrial processes. Herein, we describe a synthetic chemical strategy to produce hybrid organic/inorganic nanobiocatalysts; it exploits the self‐assembly of silane building blocks at the surface of enzymes to grow an organosilica layer, of controlled thickness, that fully shields the enzyme. Remarkably, the enzyme triggers a rearrangement of this organosilica layer into a significantly soft structure. We demonstrate that this change in stiffness correlates with the biocatalytic turnover rate, and that the organosilica layer shields the enzyme in a soft environment with a markedly enhanced resistance to denaturing stresses. Abstract : Important soft skills : Hybrid organic/inorganic nanobiocatalysts were created by the immobilization of enzymes on amino‐modified silica nanoparticles and subsequent self‐assembly and polycondensation of silane building blocks at the surface of the enzymes. The soft environment of the organosilica layer shielded the enzymes from denaturing stresses; however, the enzymes retained their conformational freedom and thus their catalytic activity (see picture).